Harry Potter and the half-blood prince - Rowling, J. K. (London : Bloomsbury, 2014)
Novice wizard Harry Potter, now sixteen years old, begins his sixth year at Hogwarts School of Witchcraft and Wizardry in the midst of the battle between good and evil, which has heated up with the return of the Dark Lord Voldemort.
"Year 6"--Spine.
Sequel to: Harry Potter and the Order of the Phoenix.
7.3
5-8.
5-8
Keywords: Hogwarts School of Witchcraft and Wizardry (Imaginary organization) -- Juvenile fiction; Magic -- Juvenile fiction; Potter, Harry (Fictitious character) -- Juvenile fiction; Schools -- Juvenile fiction; Wizards -- Juvenile fiction; Hogwarts School of Witchcraft and Wizardry (Imaginary organization) -- Fiction; Magic -- Fiction; Potter, Harry (Fictitious character) -- Fiction; Schools -- Fiction; Wizards -- Fiction; Hogwarts School of Witchcraft and Wizardry (Imaginary organization) -- Fiction; Magic -- Fiction; Potter, Harry (Fictional character) -- Fiction; School stories; Wizards -- Fiction; England -- Juvenile fiction; England -- Fiction; England -- Fiction